Successful recognition of emergency conditions of primary adrenal insufficiency in a nine-month-old girl: A case report from a tertiary hospital in Indonesia - Dewi, Karina Pharamita; Perwitasari, Rayi Kurnia; Hisbiyah, Yuni; Faizi, Muhammad; Rochmah, Nur (Edelweiss Applied Science and Technology, 2025)
Diagnosis of Adrenal Insufficiency (AI) in children is often challenging due to the relatively low incidence and non-specific presentation, so misdiagnosis often occurs, especially in emergency settings. Prompt recognition and management are crucial to reducing the morbidity and mortality linked to this potentially fatal illness, emphasizing the importance of heightened awareness among healthcare professionals. A 9-month-old girl was brought to the ER with a chief complaint of excessive vomiting. The girl presented with hyperpigmentation, leading to a suspicion of primary adrenal insufficiency secondary to Addison’s disease. Laboratory findings revealed electrolyte imbalances (hyperkalemia and hyponatremia) and metabolic acidosis due to acute kidney injury secondary to fluid loss, prompting intravenous fluid therapy and hydrocortisone administration. Following hospitalization and comprehensive evaluation, including tuberculosis screening and abdominal ultrasound, the patient showed clinical improvement and was discharged with hydrocortisone and fludrocortisone as maintenance therapy. Regular follow-ups in the endocrinology clinic ensured continued management and adjustment of medication doses to maintain stability. Adrenal insufficiency may present with a spectrum of symptoms, including gastrointestinal complaints, and its diagnosis hinges on identifying specific hormone deficiencies. Primary adrenal insufficiency (PAI) often associated with mineralocorticoid deficiency, manifests with signs such as hypotension and electrolyte abnormalities, necessitating urgent evaluation and treatment.